Fundamental principles of engineering nanometrology - Leach, R. K. (Micro & nano technologies., 2010)
The principles of engineering metrology applied to the micro- and nanoscale: essential reading for all scientists and engineers involved in the commercialisation of nanotechnology and measurement processes requiring accuracy at the nanoscale. The establishment of common standards will be an essential key to unlocking the commercial potential of Micro- and Nanotechnologies (MNT), enabling fabrication plants to interchange parts, packaging and design rules. Effectively MNT standardization will provide the micro- and nanoscale equivalents of macro-scale nuts and bolts or house bricks. Currently there is a major thrust for standardization of MNT activities, with committees of the ISO, IEC and numerous national and regional committees being set up. In this book Professor Richard Leach, of the UK's National Physical Laboratory (NPL) makes a significant contribution to standardization in the field of MNT, extending the principles of engineering metrology to the micro- and nanoscale, with a focus on dimensional and mass metrology. The principles and techniques covered in this book form the essential toolkit for scientists and engineers involved in the commercialisation of nanotechnology and measurement processes requiring accuracy at the nanoscale. Key topics covered include: Basic metrological terminology, and the highly important topic of measurement uncertainty. Instrumentation, including an introduction to the laser Measurement of length using optical interferometry, including gauge block interferometry Displacement measurement and sensors Surface texture measurement, stylus, optical and scanning probe instruments, calibration, profile and areal characterisation Coordinate metrology Low mass and force metrology About the Author Professor Richard Leach is a Principal Research Scientist in the Mass & Dimensional Group, Engineering Measurement Division at the National Physical Laboratory (NPL), UK. Provides a basic introduction to measurement and instruments & nbsp; Thoroughly presents numerous measurement techniques, from static length and displacement to surface topography, mass and force Covers multiple optical surface measuring instruments and related topics (interferometry, triangulation, confocal, variable focus, and scattering instruments) Explains, in depth, the calibration of surface topography measuring instruments (traceability; calibration of profile and areal surface texture measuring instruments; uncertainties) Discusses the material in a way that is comprehensible to even those with only a limited mathematical knowledge.